Effect on Auxins (IAA, IBA and NAA) on Rooting Behaviour of Grewia optiva Burrett Stem Cuttings under Intermittent Mist - Shamet, G. S.; Dhiman, R. C. (Indian Forester, 1991)
Grewia optiva Burretta fodder cum fuel species can be propagated successfully by stem cuttlngs under Intermittent mist. Soaking the cutting base for 20 hours In 100 mg/l IAA has given a maximum rooling of 77.5 per cent in June. The technique can be used for mass multiplication of superior clones foroperational rooting of the species for plantation and seed orchard establishment.